Pengaruh Komitmen Organisasional terhadap Resistance to Change di Organisasi Sektor Publik - Nasih, Moh. (BISMA (Bisnis dan Manajemen), 2018)
Changes in the organizational environment sometimes is needed and even inevitable. Local government as one of the public sector organizations also deal with the changes. One of the changes faced by the public sector is a change from the cash basis accounting system into accrual basis. This study examines the effect of organizational commitment on resistance to change of local civil servants. The total sample of this study used a total of 77 respondents from one local government in East Java. This study found that higher normative commitment of local government employees, level of resistance to change will be lower. This study didnt found any effect of afective commitment and continuance commitment to the resistance to change